THE INVESTIGATION OF OCCASIONALISMS BASED ON ICONIC AND MODERN WORKS - Vdovichenko, Y.S. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
This article is devoted to the study of occasionalisms and author's neologisms in modern English, their usage in various cult and contemporary works. The article reveals the connection between word-formative models, used in creating author‘s neologisms, and occasional words into the English language. The aim of the work is to determine the role of occasionalisms as a means of expression. The object of this study is occasionalisms in literary texts in English, and the subject of research is the features of the use of occasionalisms in literary texts. The definition of the role of occasionalisms has helped to show their significance and importance as means of expression in modern English.
Keywords: occasionalism; potential word; word-formation; nonce words; occasional words